Design and Testing of Autonomous Chargeable and Wearable Sweat/Ionic Liquid‐Based Supercapacitors. Issue 25 (10th July 2022) - Selvam, Samayanan; Park, Young‐Kwon; Yim, Jin‐Heong
Abstract: This work demonstrates ionic liquid electrolyte‐inscribed sweat‐based dual electrolyte functioning supercapacitors capable of self‐charging through sweat electrolyte function under a non‐enzymatic route. The supercapacitor electrodes are fabricated from TREN (tris(2‐aminoethyl)amine), poly‐3, 4‐ethylenedioxythiophene, and a graphene oxide mixture with copper‐mediated chelate, and this polymer‐GO‐metal chelate film can produce excellent energy harvest/storage performance from a sweat and ionic liquid integrated electrolyte system. The fabricated device is specifically designed to reduce deterioration using a typical planar structure. In the presence of sweat with ionic liquid, the dual electrolyte mode supercapacitor exhibits a maximum areal capacitance of 3600 mF cm −2, and the energy density is 450 mWhcm −2, which is more than 100 times greater than that from previously reported supercapacitors. The supercapacitors were fabricated/attached directly to textile fabrics as well as ITO‐PET (Indium tin oxide (ITO)‐polyethylene terephthalate (PET) film to study their performance on the human body during exercise. The self‐charging performance with respect to sweat wetting time for the sweat@ionic liquid dual electrolyte showed that the supercapacitor performed well on both fabric and film. These devices exhibited good response for pH effect and biocompatibility, and as such present a promising multi‐functional energy system as a stable power source for next‐generation wearable smart electronics. Abstract : This work demonstrates ionic liquid electrolyte‐inscribed sweat‐based dual electrolyte functioning supercapacitors capable of self‐charging through sweat electrolyte function. The supercapacitors are fabricated/attached directly to textile fabrics as well as Indium tin oxide (ITO)‐polyethylene terephthalate (PET) film to study their performance on the human body during exercise with excellent energy harvest/storage performance for a conformable on‐skin various energy storage devices.